Investıgation of Virtual World Risk Perceptions of Individuals Interested in Team and Individual Sports - TAPŞIN , Fuat Orkun; KARAGÜN, Elif (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2024)
This study aims to investigate the risk perceptions of individuals who have an interest in both team and individual sports within the virtual world. The study has been structured utilizing the quantitative research methodology of a survey model. The study involved 207 participants who are avid users of smartphones and social media, and who have shown a keen interest in team or individual sports. The study was carried out at the sports facilities located in the Serdivan district of Sakarya province. The data collection process utilized the Virtual World Risk Perception Scale, a tool developed by Arslankara and Usta (2018), to assess individuals’ perception of risk in virtual environments. In addition, a personal information form consisting of 8 items was administered to collect socio-demographic data. The data has been analyzed utilizing the SPSS 25.00 software package. Calculations have been performed to determine the frequencies, means, standard deviations, and percentage distributions of the socio-demographic characteristics of the participants. Given that the data followed a normal distribution, the analysis focused on virtual world risk perceptions of participants in team and individual sports, taking into account their sociodemographic characteristics. The independent samples t-test was employed for making pairwise comparisons, whereas the oneway analysis of variance (ANOVA) test was utilized for comparisons that involved more than two groups. The Tukey test was employed to determine the origin of the difference between groups, as indicated by the results of the variance analysis. Overall, there were no significant differences observed in any of the sub-dimensions of the virtual world risk perception scale when considering participants’ educational background and their involvement in either individual or team sports. Regarding gender, women exhibited a greater perception of virtual opportunities, whereas men displayed a higher perception of virtual corruption. University graduates exhibited a greater perception of virtual opportunities and virtual awareness. Participants in all occupations exhibited a greater perception of virtual opportunities, virtual exhaustion, and virtual awareness. Individuals who were 32 years old or older exhibited a greater perception of virtual opportunities and virtual awareness. Individuals with a moderate income level exhibited a greater perception of virtual opportunities. Moreover, there was a substantial rise in the sub-dimensions of virtual opportunities for individuals who spent 5 hours or more using social media.